SPECIFICITY OF TEACHING THE UZBEK LANGUAGE AS UNGENERAL (ON THE EXAMPLE OF THE DEVELOPMENT OF SPEAKING) - Abdukhalilova Dilrabo Nematjonovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the pedagogical conditions for the formation of a culture of communication between children in primary grades, ways of implementing it in the educational process.